Oral pathogen candida in patients under antineoplastic therapies - Rebolledo-Cobos, Martha; Sánchez-Molina, Marisol (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Cancer control treatments are aimed at prolonging patient survival, but they also trigger inevitable and irreversible side effects, often infectious in nature, complicating the prognosis of the oncological disease. These include the pathogenic behavior of Candida, with Albicans being its most common species in the oral mucosa. Albicans is considered a commensal fungus that, as a result of the neutropenia resulting from antineoplastic therapies, behaves as an opportunistic entity causing candidiasis. This fungal infection has aggravating factors for the patient, such as xerostomia and hyposalivation, infections like dental caries, and other factors such as improper oral hygiene. Several consulted authors highlight the presence of Candida, its different species and oral candidiasis as a microorganism and classic opportunistic infection in immunosuppressed patients, and even more in those subjected to antineoplastic treatments. The aim of this review is to describe the pathogenic behavior of Candida in the oral mucosa of patients under antineoplastic treatments.